2002
DOI: 10.1203/00006450-200207000-00005
|View full text |Cite
|
Sign up to set email alerts
|

1α,25(OH)2D3 Inhibits Not Only Th1 But Also Th2 Differentiation in Human Cord Blood T Cells

Abstract: (M.P., M.W.) Human naive CD4 ϩ T helper (Th) and CD8 ϩ cytotoxic (Tc) T cells, which only produce IL-2, may differentiate into Th1/Tc1-or Th2/Tc2-like lymphocytes, characterized by their cytokine production profile. 1␣,25-dihydroxyvitamin D 3 (1␣,25(OH) 2 D 3 ) has been reported to inhibit Th1/Tc1-related, but increase Th2/ Tc2-associated cytokines in T cells from adults. In industrialized countries, vitamin D supplementation for prevention of rickets is initiated within the first days of life and continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 65 publications
5
80
2
Order By: Relevance
“…Vitamin D has well-known inhibitory effects on certain immune cells, including T cell proliferation and CD8 cell cytotoxicity. Both Th1 and Th2 cells are also direct targets of vitamin D. Vitamin D and vitamin D-receptor deficiencies are associated with elevated Th1 responses, whereas vitamin D supplementation results in a shift of the Th1/Th2 balance toward Th2-cell responses (187,188). The active form of vitamin D seems to promote the induction of Foxp3 Treg and T regulatory 1 cells and is therefore implicated in the control of autoimmunity (189).…”
Section: Summary Of Findings For Zincmentioning
confidence: 99%
“…Vitamin D has well-known inhibitory effects on certain immune cells, including T cell proliferation and CD8 cell cytotoxicity. Both Th1 and Th2 cells are also direct targets of vitamin D. Vitamin D and vitamin D-receptor deficiencies are associated with elevated Th1 responses, whereas vitamin D supplementation results in a shift of the Th1/Th2 balance toward Th2-cell responses (187,188). The active form of vitamin D seems to promote the induction of Foxp3 Treg and T regulatory 1 cells and is therefore implicated in the control of autoimmunity (189).…”
Section: Summary Of Findings For Zincmentioning
confidence: 99%
“…At birth, cord serum 25(OH)D levels are directly correlated with levels of IL-10, an immunosuppressive cytokine [57]. In vitro studies show that 1,25(OH) 2 D acts on naïve T cells to retard their development into either T helper 1 or 2 cells [58]. …”
Section: Vitamin D Status During Pregnancy and The Effects On Offsmentioning
confidence: 99%
“…In vitro studies have shown that 1,25-dihydroxyvitaminD3, the active metabolite of vitamin D, is important for promoting and regulating immune responses [5,6]. Observational studies suggest a link between low vitamin D concentrations and an increased risk of lower and upper respiratory tract infections in infants and young children [7].…”
Section: Introductionmentioning
confidence: 99%